Whistleblower Protection Act 2010: Protecting whistleblower in Malaysia on disclosure of information through mass media / Khalam Syamir Mohd and Yusmarliny Jasmin - Mohd, Khalam Syamir; Jasmin, Yusmarliny (Faculty of Law, 2015)
In 15 December 2010, Whistleblower Protection Act has officially enacted and enforced which purposely to protect whistleblowers in Malaysia. Ideally, it is one of the Malaysian Government’s efforts towards tackling corruption and promoting good governance. However, upon certain circumstances, particularly to disclosure made to the mass media, the protection will not be given to the whistleblower. This will discourage citizens to whistleblowing as it deemed as not in their favor. Prior to this issue, researchers decided to conduct the study on the application of the protection given to the whistleblower. Research revolved on the comparison between the Whistleblower Protection Act in Malaysia and Public Interest Disclosure Act of United Kingdom since the legislation in Malaysia is derived from and being pari material with the legislation of the United Kingdom. Different sources have been obtained in achieving the purpose of this study. The research was done by reference to the legislations that are the Malaysia’s Whistleblower Protection Act 2010, as well as the Public Interest Disclosure Act 1998 in United Kingdom. Besides, despite of the digital sources from the internet, the reference to the case study, books, journals and newspaper articles was also used in order to gain more information regarding the decided topic. Towards the end of the study, researchers come up with the suggestion on how to overcome the weakness and to improvise the effectiveness of protection given to the whistleblower that blows the whistle to the mass media in Malaysian Legislation.